A note on stray light in the Tübingen perimeter. Issue 2 (February 1977) - Weale, R A; Wheeler, C
Abstract : Measurements were made of the relative intensity of light scattered in the neighbourhood of the large and small targets on the Tübingen perimeter. Two target intensities were studied. The scattered light fraction ranged from 0-1 to 25% and its effect was detected more readily by young than by older observers.